2019
DOI: 10.1016/j.ijcard.2018.12.061
|View full text |Cite
|
Sign up to set email alerts
|

Elevated renalase levels in patients with acute coronary microvascular dysfunction – A possible biomarker for ischemia

Abstract: Aims We explored the relationship between inflammation, renalase an anti-inflammatory protein, and acute chest pain with coronary microvascular dysfunction (CMD). Methods and Results We used cardiac Rb-82 PET/CT imaging to diagnose coronary artery disease (CAD/CALC) (defect or coronary calcification) and CMD (depressed coronary flow reserve without CAD) in patients with chest pain in an emergency department (ED). Blood samples were collected pre-imaging within 24 hours of ED presentation and were analyzed fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 41 publications
(41 reference statements)
0
18
0
Order By: Relevance
“…This is, truly, the very first study to review and confirm the prognostic potential of renalase for ischemia, regarding the ejection fraction stratification. Likewise, impressive evidence has recently implicated renalase as a possible biomarker for ischemia ( 5 , 14 , 16 18 , 25 27 ). The obtained findings may add considerably to the growing body of literature in this field.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is, truly, the very first study to review and confirm the prognostic potential of renalase for ischemia, regarding the ejection fraction stratification. Likewise, impressive evidence has recently implicated renalase as a possible biomarker for ischemia ( 5 , 14 , 16 18 , 25 27 ). The obtained findings may add considerably to the growing body of literature in this field.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, substantial evidence showed that functional polymorphisms of the renalase gene were associated with cardiac hypertrophy in patients with aortic stenosis ( 8 ) and an increased risk of CAD in the general population ( 9 ) and in hemodialyzed patients ( 10 ), patients with hypertension and associated CAD ( 11 ), patients with unstable angina pectoris and concomitant metabolic syndrome ( 12 ), and in patients with stable CAD, presenting with cardiac hypertrophy, ventricular dysfunction, and inducible ischemia ( 13 ). Moreover, renalase has been suggested as a prognostic biomarker for ischemia in patients with acute coronary microvascular dysfunction ( 14 ) and as a predictor for all-cause mortality in chronic kidney disease ( 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…Patients with acute chest pain who were found to have CMD, as assessed by reduced PET-derived CFR, but no evidence of CAD had elevated levels of serum renalase, an anti-inflammatory protein released from the heart and kidneys in response to acute ischaemic stress. [ 51 ] Of note, these patients had similar concentrations of serum inflammatory markers (CRP, TNF-α, vascular endothelial growth factor, IL-1β, IL-6 and metalloproteinases) as control patients. [ 51 ] These findings imply the dynamic nature of the inflammatory response to an acute ischaemic insult compared with chronic coronary syndrome.…”
Section: Inflammatory Modulators Of Coronary Vascular Function: Beyond a Marker?mentioning
confidence: 99%
“…[ 51 ] Of note, these patients had similar concentrations of serum inflammatory markers (CRP, TNF-α, vascular endothelial growth factor, IL-1β, IL-6 and metalloproteinases) as control patients. [ 51 ] These findings imply the dynamic nature of the inflammatory response to an acute ischaemic insult compared with chronic coronary syndrome. [ 51 ]…”
Section: Inflammatory Modulators Of Coronary Vascular Function: Beyond a Marker?mentioning
confidence: 99%
See 1 more Smart Citation